The architecture of players in Ghana’s digitalising agriculture. - Akorsu, Angela Dziedzom; Britwum, Akua Opokua (Southern Centre for Inequality Studies (SCIS), 2022)
Digital technology is hailed as the appropriate solution for facilitating the deployment of solutions to poor farmers in Ghana in face of the state’s inability to provide the required extension personnel. The influx of digital platforms into Ghana has brought in several operators whose connections and what they portend for Ghanaian farmers are under investigation. Using the food regimes approach we explore how digital technologies have been introduced into Ghana’s agricultural landscape. Our interest was the developing discourses used to legitimate the transition of agricultural digitalisation from a public good critical for ending rural poverty to a commodity for which farmers assume full costs. Our data was drawn from individual and group interviews with digital players in Ghana’s capital city. We obtained additional data from secondary sources including websites and research publications. We contend that the high proliferation of agritechs in Ghana in the face of state withdrawal locks them into the international digital ecosystems riding on the social enterprise discourse to sanitise the exploitation of Ghanaian farmers. In the face of the complex interconnectedness of digital players, there is an urgent need for sharper conceptual tools to move analysis to the conceptualisation of development alternatives to ensure the beneficial impact of digital technologies for poor farmers in countries such as Ghana.
Keywords: Gig Economy; Inequality; Digital Labor Platforms; Agricultural extension services; Food regimes; Ghana; Digital agriculture